2014
DOI: 10.1021/ja506385p
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Bond Energies and Microtubule Biomechanics Determined from Nanoindentation in Silico

Abstract: Microtubules, the primary components of the chromosome segregation machinery, are stabilized by longitudinal and lateral noncovalent bonds between the tubulin subunits. However, the thermodynamics of these bonds and the microtubule physicochemical properties are poorly understood. Here, we explore the biomechanics of microtubule polymers using multiscale computational modeling and nanoindentations in silico of a contiguous microtubule fragment. A close match between the simulated and experimental force–deforma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
113
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(134 citation statements)
references
References 66 publications
19
113
2
Order By: Relevance
“…Here the work done by the two kinesin motors will be ~8 × 10 −20 J, which needs to be sufficient to break two lateral tubulin-tubulin bonds (the tails are C-shaped and connected on the top and bottom of the C’s in the MT), or ~4 × 10 −20 J of work to split apart a single lateral tubulin-tubulin bond. This value is in reasonable agreement with that determined from in silico modeling of 4.8 × 10 −20 J (6.9 ± 0.4 kcal/mol) for this bond32, suggesting that having one motor on each end might be sufficient to split the MT. At high motor surface densities, there are likely more than one motor on each end, which would produce ample force to split the MT.…”
Section: Discussionsupporting
confidence: 89%
“…Here the work done by the two kinesin motors will be ~8 × 10 −20 J, which needs to be sufficient to break two lateral tubulin-tubulin bonds (the tails are C-shaped and connected on the top and bottom of the C’s in the MT), or ~4 × 10 −20 J of work to split apart a single lateral tubulin-tubulin bond. This value is in reasonable agreement with that determined from in silico modeling of 4.8 × 10 −20 J (6.9 ± 0.4 kcal/mol) for this bond32, suggesting that having one motor on each end might be sufficient to split the MT. At high motor surface densities, there are likely more than one motor on each end, which would produce ample force to split the MT.…”
Section: Discussionsupporting
confidence: 89%
“…As we showed in our recent study 38 Table 2). As we demonstrated previously [35][36][37] , the entropy increase observed in the course of forced deformation is accompanied by the increase in the capsid stiffness, which occurs due to remodeling of the shell structure, whose protein subunits tend to re-arrange underneath the cantilever tip. Subsequent Crooks theorem based estimation of the reversible deformation work revealed that the large ~1 Mcal/mol free energy is required to induce structural collapse of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 17 nanocompartment.…”
Section: Encapsulin Provides a Mechanically Rigid And Resilient Biomasupporting
confidence: 64%
“…This approach uniquely combines the all-atom Molecular Dynamics simulations of atomic structural models of biological particles and the Langevin simulations of their native-topology based Self-Organized Polymer (SOP)33, 34 coarse-grained reconstructions (see Supplementary Methods). We employed this approach in earlier work to explore the biomechanical properties of virus particles and microtubule polymers[35][36][37] . The use of high-performance computing on Graphics Processing Units (GPUs)33,37,46 has enabled us to perform nanoindentations in silico on the millisecond time…”
mentioning
confidence: 99%
“…Here, we used the SOP model [13] with modifications for CACs and Brownian Dynamics to investigate the rupture dynamics in the mechanical unbinding of LFA-1 from ICAM-1 and ICAM-3. Several previous studies [14][15][16][17][18][19][20][21]. in a variety of systems (proteins, RNA, viruses, and complexes) have established that simulations based on the coarse-grained Self-Organized Polymer (SOP) model have provided a molecular bases for interpreting and predicting the outcomes of experiments.…”
Section: Introductionmentioning
confidence: 99%